T Follicular Helper-Like Cells in Inflamed Non-Lymphoid Tissues - Hutloff, Andreas (Frontiers in Immunology, 2018)
T and B cell cooperation normally takes place in secondary lymphoid organs. However, both cell types are also frequently found in inflamed non-lymphoid tissues. Under certain conditions, these infiltrates develop into ectopic lymphoid structures, also known as tertiary lymphoid tissues, which structurally and functionally fully resemble germinal centers in secondary lymphoid organs. However, tertiary lymphoid tissue is uncommon in most human autoimmune conditions; instead, relatively unstructured T and B cell infiltrates are found. Recent studies have demonstrated that active T and B cell cooperation can also take place in such unstructured aggregates. The infiltrating cells contain a population of T follicular helper- (Tfh-) like cells (also designated "peripheral T helper cells") lacking prototypic Tfh markers like CXCR5 and Bcl-6 but nevertheless expressing high levels of molecules important for B cell help like IL-21 and CD40L. Moreover, Tfh-like cells isolated from inflamed tissues can drive the differentiation of B cells into antibody-secreting cells in vitro. These findings are not restricted to experimental animal models but have been reproduced in rheumatoid arthritis and breast cancer patients. At this point it is unclear whether T and B cell cooperation outside the ordered structure of the germinal center fully mirrors the reactions in secondary lymphoid organs. However, Tfh-like cells in inflamed tissues are certainly important for the local differentiation of B cells into antibody-secreting cells, and should be considered as an important target for the treatment of autoimmune diseases.